Brief environmental enrichment elicits metaplasticity of hippocampal synaptic potentiation in vivo - Manahan-Vaughan, Denise; Buschler, Arne (Frontiers in Behavioral Neuroscience, 2012)
Long-term environmental enrichment (EE) elicits enduring effects on the adult brain, including altered synaptic plasticity. Synaptic plasticity may underlie memory formation and includes robust (>24h) and weak (<2h) forms of long-term potentiation (LTP) and long-term depression (LTD). Most studies of the effect of EE on synaptic efficacy have examined the consequences of very prolonged EE-exposure. It is unclear whether brief exposure to EE can alter synaptic plasticity. Clarifying this issue could help develop strategies to address cognitive deficits arising from neglect in children or adults. We assessed whether short-term EE elicits alterations in hippocampal synaptic plasticity and if social context may play a role. Adult mice were exposed to EE for 14 consecutive days. We found that robust late-LTP (>24h) and short-term depression (<2h) at Schaffer-collateral-CA1 synapses in freely behaving mice were unaltered, whereas early-LTP (E-LTP, <2h) was significantly enhanced by EE. Effects were transient: E-LTP returned to control levels 1 week after cessation of EE. Six weeks later animals were re-exposed to EE for 14d. Under these conditions, E-LTP was facilitated into L-LTP (>24h), suggesting that metaplasticity was induced during the first EE experience and that EE-mediated modifications are cumulative. Effects were absent in mice that underwent solitary enrichment or were group-housed without EE. These data suggest that EE in naïve animals strengthens E-LTP, and also promotes L-LTP in animals that underwent EE in the past. This indicates that brief exposure to EE, particularly under social conditions can elicit lasting positive effects on synaptic strength that may have beneficial consequences for cognition that depends on synaptic plasticity.